Substituted dipyridophenazine complexes of Cr(III): synthesis, enantiomeric resolution and binding interactions with calf thymus DNA. - KELLY, JOHN; MCCABE, THOMAS (My University, 2010)
[Cr(phen)2(X2dppz)]3+ {X = H, Me, or F} have been synthesised, characterised, and chromatographically resolved into their constituent ? and ? enantiomers. The DNA-binding interactions of each of the racemic complexes were investigated, with the results of linear dichroism, thermal denaturation, and emission quenching studies indicative of intercalative binding to CT-DNA with a significant electrostatic contribution. UV/Vis absorption titrations suggest strong DNA binding by each of the racemic complexes, with the methylated analogue [Cr(phen)2(Me2dppz)]3+ exhibiting the largest equilibrium binding constant. Emission quenching and UV-Vis titrations of the enantiomers of [Cr(phen)2(dppz)]3+ imply similar binding affinities for the ? and ? isomers, although significant differences between the circular dichroism spectra of the enantiomers in the presence of DNA connote differences in binding orientation and/or conformation between the two.
PUBLISHED
Keywords: Genetics; Cr(III); Genes & Society